Retrograde Bladder Filling After Outpatient Gynecologic Surgery: A Systematic Review and Meta-analysis. Issue 4 (October 2021) - Thiel, Peter S.; Mathur, Siddhi; Zakhari, Andrew; Matelski, John; Walsh, Chris; Murji, Ally
Abstract : OBJECTIVE: To systematically review and meta-analyze randomized controlled trials (RCTs) comparing postoperative bladder retrofilling to passive filling after outpatient gynecologic surgery to evaluate effects on postoperative outcomes. DATA SOURCES: We searched MEDLINE, PubMed, Cochrane Central Register of Controlled Trials (CENTRAL), EMBASE, and ClinicalTrials.gov from 1947 to August 2020. METHODS OF STUDY SELECTION: Two reviewers screened 1, 465 articles. We included RCTs that compared postoperative bladder retrofilling to passive filling in patients who underwent outpatient gynecologic surgery by any approach. The primary outcome was the time to first void. Secondary outcomes included time to discharge, postoperative urinary retention, urinary tract infection, and patient satisfaction. Mean differences and relative risks (RRs) were calculated for the meta-analysis. Risk of bias was assessed using the Cochrane Risk of Bias Tool. TABULATION, INTEGRATION, AND RESULTS: We included eight studies with 1, 173 patients. Bladder retrofilling in the operating room resulted in a significant decrease in the time to first void (mean difference −33.5 minutes; 95% CI −49.1 to −17.9, 4 studies, 403 patients) and time to discharge (mean difference –32.0 minutes; 95% CI −51.5 to −12.6, eight studies, 1, 164 patients). Bladder retrofilling did not shorten time to discharge when performed in the postanesthetic care unit (mean difference –14.8 min; 95% CI −62.6 to 32.9, three studies, 258 patients) or after laparoscopic hysterectomy (mean difference –26.0 min; 95% CI −56.5 to 4.5, five studies, 657 patients). There were no differences in postoperative urinary retention (RR 0.77; 95% CI 0.45–1.30, five studies, 910 patients) or risk of urinary tract infection between the retrofill and passive fill groups (RR 0.50; 95% CI 0.14–1.77, four studies, 387 patients). Patient satisfaction was comparable between groups. CONCLUSION: Retrofilling the bladder in the operating room after outpatient gynecologic surgery modestly reduces the time to first void and discharge with no increase in adverse events. SYSTEMATIC REVIEW REGISTRATION: PROSPERO, CRD42020203692. Abstract : Retrofilling the bladder in the operating room after outpatient gynecologic surgery reduces the time to first void and discharge with no increase in adverse events.